The evolution of gene regulation in mammalian cerebellum development [research data] - Sarropoulos, Ioannis; Sepp, Mari; Yamada, Tetsuya; Schäfer, Philipp; Trost, Nils; Schmidt, Julia; Schneider, Céline; Drummer, Charis; Mißbach, Sophie; Taskiran, Ibrahim I.; Hecker, Nikolai; González-Blas, Carmen Bravo; et al. (Universität, 2025)
Gene regulatory changes are considered major drivers of evolutionary innovations, including the cerebellum’s expansion during human evolution, yet they remain largely unexplored. In this study, we combined single-nucleus measurements of gene expression and chromatin accessibility from six mammals (human, bonobo, macaque, marmoset, mouse, and opossum) to uncover conserved and diverged regulatory networks in cerebellum development. We identified core regulators of cell identity and developed sequence-based models that revealed conserved regulatory codes. By predicting chromatin accessibility across 240 mammalian species, we reconstructed the evolutionary histories of human cis-regulatory elements, identifying sets associated with positive selection and gene expression changes, including the recent gain of THRB expression in cerebellar progenitor cells. Collectively, our work reveals the shared and mammalian lineage-specific regulatory programs governing cerebellum development.
Gefördert durch: European Research Council (ERC): VerteBrain, grant agreement no. 101019268; European Research Council (ERC): BRAIN-MATCH, grant agreement no. 819894; European Research Council (ERC): OntoTransEvol, grant agreement no. 615253
Gesehen am 30.09.2025
Keywords: Forschungsdaten; Datenbank